Quality of Plague Surveillance System in Pasuruan Regency Year 2014 Based on Surveillance Attributes - Siti Malikhatin; Lucia Yovita Hendrati (Jurnal Berkala Epidemiologi, 2017)
Plague is a quarantine zoonosis disease that still occurs in Pasuruan Regency. Plague suspects were still found until 2013. Plague surveillance carried out includes human and rodent surveillance. An evaluation of the surveillance system needs to be done to improve the quality, efficiency, and usefulness of the surveillance system itself. The purpose of this study was to assess the quality of the Plague surveillance system in 2014 based on its attributes, namely simplicity, flexibility, acceptability, data quality, sensitivity, positive predictive value, representativeness, timeliness, and stability. The design of this study is an evaluation study. The subject was the Plague surveillance system in Pasuruan Regency throughout 2014. Data collection was carried out using interviews, observation, and document review techniques. The data and information obtained are compared with existing guidelines and theories then presented in the form of narratives, tables, and images. The results show that the existing surveillance system is simple and flexible, low data quality and acceptability, positive predictive value and sensitivity cannot be measured, low representativeness and timeliness, and high stability. The conclusion that can be drawn is the quality of the Plague surveillance system in Pasuruan Regency based on its attributes is still not good, so it is advisable to conduct training, provide sufficient funds, monitor and evaluate periodically, disseminate information to cross sectors, cross programs, and the community, sending reports e-mail surveillance, using spreadsheet software for rodent surveillance reports, refining reports by including information on damaged serum, a serum that is not in accordance with the number of rodent catches, and traps lost.